The Libraries of Preacher Brethren of Gidle, Łęczyca, Łowicz, Piotrków Trybunalski and Sieradz and Their Book Collections in the 17th century: A Comparative Analysis - Stolarczyk, Tomasz (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The aim of the hereby article is to present the epitome of Dominican Convent libraries situatedwithin the area of the former archdeaconry of Łęczyca: in Gidle, Łęczyca, Łowicz, Piotrków Trybunalskiand Sieradz, as well as their book collection originating from XVII century. They were functioning sincethe monasteries were funded, the evidence of what is the existence of Dominican schools which couldnot do without libraries. Extra thought was given to the books at the Order of Preacher Brethren, whichis expressed in its legislation. Disobedience to the library rules resulted in severe consequences including excommunication. The analysis of the mentioned book resources was carried out on the basis of Latinlibrary inventories from the 17th century, which were included in the codex of Preacher Brethren ofŁęczyca, Łowicz and Piotrków and Gidle inventory created in the beginning of XX century. All thoseinventories are now stored in the archives of the Polish Province of Dominicans in Kraków. The largestbook collection was in the possession of Sieradz Dominicans — about 400 volumes. The second largestcollection was in Gidle library with 345 volumes. In third position was the library of Łowicz Conventwhich collection comprised 294 volumes. The fourth biggest library was the library in Piotrków whichstored 215 volumes. In the Łęczyca library there were about 100 volumes in the beginning of XVIIcentury.